Land policy instruments in conditions of market-oriented economy and in pluralism of properties - Rakar, Albin (Geodetski vestnik, 1994)
The article presents the current state in the field of land policy and physical planning in Slovenia and enumerates needs and possibilities for some not directive instruments. Of the latter, the article deals with more detail only building-grounds stock forming and land redistribution
Keywords: geodezija; stavbna zemljišča; urejanje prostora; zemljiška politika